O35 WHAT HAPPENS TO PATIENTS WITH ACUTELY SYMPTOMATIC HERNIA IN THE UK? FINDINGS FROM THE MASH STUDY. (25th November 2021) - Proctor, Victoria; Spence, Olivia; Burns, Flora; Green, Susanna; Sayers, Adele; Smart, Neil; Lee, Matthew
Abstract: Aim: Acutely symptomatic abdominal wall and groin hernias (ASH) are a common reason for acute surgical admissions in the UK. There is limited data to guide the treatment of such presentations. This study aimed to assess outcomes of emergency hernia surgery, and identify common management strategies, to improve care for these high-risk patients. Material and Methods: A 12 week, UK-based, multi-centre, collaborative, prospective cohort study (NCT04197271) recruited adults with ASH. Data on patient characteristics, inpatient management, quality of life, complications and wound healing was collected. 30 and 90-day follow-up phone calls assessed complications and quality of life. Descriptive analyses were performed to describe population and outcomes. Results: Twenty-three acute Trusts recruited 268 patients. Inguinal (37.7%) and umbilical (37.7%) were the most common hernia locations. 13.4% were awaiting elective surgery and 13.1% had been previously declined intervention. CT was performed in 48%. 82% underwent surgical management with open repair (94%) under general anaesthesia (93%) being most common. 4/11 laparoscopic procedures were converted to open. 55% of repairs used mesh, typically synthetic non-absorbable (87%). Complications were infrequent with surgical site infection (9.4%), delirium (3.2%) and pneumonia (2.3%) being most common. Mortality was 1.5%. Immediate surgical management was associated with significant improvement in quality of life at 30 days. Conclusions: There is variation in the investigation, management and surgical strategy to treat acutely symptomatic abdominal wall and groin hernias in the UK. Further large-scale work is needed to establish the optimal management strategy for specific acute presentations given the wide variation at present.